PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Indeks SRI-KEHATI Periode 2021-2023) - Tegar Ananta Yudha; Jaka Isgiyarta (Diponegoro Journal of Accounting, 2026)
This study addresses the inconsistency in prior research and the limited flow of sustainable investments in developing nations like Indonesia. Its primary objective is to examine the impact of Environmental, Social, and Governance (ESG) disclosures—both holistically and individually—on firm value, while also analyzing the role of audit quality as a moderating variable.The research focuses on non-financial companies consistently listed on the Indonesia Stock Exchange’s (IDX) SRI-KEHATI index from 2021 to 2023. Utilizing a purposive sampling method, a total of 54 observations were analyzed. The hypothesis testing was conducted using panel data regression with a Fixed Effect Model (FEM) and Moderated Regression Analysis (MRA) via EViews 13 software.The findings reveal that holistic ESG disclosures, alongside specific environmental and social disclosures, significantly and negatively impact firm value, whereas governance disclosure shows no effect. Furthermore, audit quality fails to moderate this relationship, concluding that stakeholders in the Indonesian capital market remain predominantly driven by short-term financial metrics rather than recognizing sustainability practices as strategic added value